2020
DOI: 10.3906/tar-1902-36
|View full text |Cite
|
Sign up to set email alerts
|

Study of the physicochemical properties of highbush blueberry and wild bilberry fruit in central Bosnia

Abstract: Although around the globe numerous studies have been conducted on the nutritional composition of blueberry/bilberry and its effect on human health, very little is known about the fruit in Bosnia and Herzegovina. This is the first report regarding the physical and chemical characteristics of the cultivated highbush blueberry and bilberry harvested in the same climatic conditions in Bosnia and Herzegovina. In this paper we present the physical (weight) and chemical (soluble solids content, total sugars, titratab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
3
8
0
2
Order By: Relevance
“…The pH of blueberries had a mean value of 3.39 and increased from 3.14 (16-1-26 hybrid) to 3.89 (16-1-16 hybrid). Similar data were reported by Aliman et al who found values for pH of 3.2–3.6 for the highbush blueberry and wild bilberry fruit grown in central Bosnia and Zorenc et al who found values for pH of 2.76–3.89 for the highbush blueberry fruits of three traditionally cultivated cultivars in Slovenia, ‘Bluecrop’, ‘Earliblue’, and ‘Jersey’.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The pH of blueberries had a mean value of 3.39 and increased from 3.14 (16-1-26 hybrid) to 3.89 (16-1-16 hybrid). Similar data were reported by Aliman et al who found values for pH of 3.2–3.6 for the highbush blueberry and wild bilberry fruit grown in central Bosnia and Zorenc et al who found values for pH of 2.76–3.89 for the highbush blueberry fruits of three traditionally cultivated cultivars in Slovenia, ‘Bluecrop’, ‘Earliblue’, and ‘Jersey’.…”
Section: Resultssupporting
confidence: 85%
“…The total phenolic content in blueberry fruits from 45 commercial cultivars grown in Suwon, Korea ranged from 170.9 to 385.7 mg GAE/100 g FW . Lee et al obtained values for the total polyphenol content between 367 and 1286 mg GAE/100 g FW for Vaccinium membranaceum species and 677–1054 mg GAE/100 g FW for Vaccinium ovalifolium species, native to Pacific Northwest of North America.…”
Section: Resultsmentioning
confidence: 99%
“…The mean TPC values in our bilberry populations fell within the reported results for bilberries from other countries and regions, such as: 403 mg GAE/100 g FW in Borja [57] and 431-455 mg GAE/100 g FW in Bugojno, Bosnia and Herzegovina [58]; 376-476 mg GAE/100 g FW in Rakitovo-Yundola, Bulgaria [59]; 392-524 in northeast Montenegro [17]; 366-457 mg GAE/100g FW in Mazovia, Polonia [60]; 387 mg GAE/100 g FW in Dragacevo, Serbia [30]; 367-442 mg GAE/100 g FW in Velka Fatra and Tatra, Slovakia [16]. During the study, the yearly values of TPC for most bilberry populations were higher compared to the results of 200-215 mg GAE/100 g FW obtained in bilberries from northeast Turkey [61].…”
Section: Discussionsupporting
confidence: 89%
“…The most dominant acid contained in bananas is malic acid [16]. Aliman et al (2020), blueberries have a total acid content of 0.93% with organic acid components such as ascorbic acid and citric acid as the largest organic acid components. The mean values followed by the same letter are not significantly different(p≤0,05).…”
Section: Total Acidmentioning
confidence: 99%